Sustainable Democratic Constitutionalism and Climate Crisis - Tully, James (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2020)
We know that law is a major enabler of the human activities that cause climate change, biodiversity destruction, and related ecosocial crises. We also turn to the law to regulate, mitigate, and attempt to transform these unsustainable human activities and systems. Yet, these regulatory regimes are often “recaptured” or “overridden” in turn by the very anthropogenic processes causing the crises. The resulting vicious cycles constitute the global trilemma of the twenty-first century that is rapidly rendering the living earth uninhabitable for humans, in radically unequal ways, and for thousands of other species. Integral, non-violent, sustainable democratic constitutionalism is one modest, experimental, trial-and-error response to this trilemma.